Protectionism through Exporting: Subsidies with Export Share Requirements in China - Fabrice Defever; Alejandro Ria\~no (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the effect of subsidies subject to export share requirements (ESR) | that is, conditioned on a firm exporting at least a given fraction of its output - on exports, the intensity of competition and welfare, through the lens of a two-country model of trade with heterogeneous firms. Our calibrated model suggests that this type of subsidy boosts exports more and provides greater protection for domestic firms than a standard unconditional export subsidy, albeit at a substantial welfare cost.
Keywords: F12; F13; O47; 330; export share requirements; export subsidies; trade policy; heterogeneous firms; China